BK Channel Dysfunction in Diabetic Coronary Artery: Role of the E3 Ubiquitin Ligases - Qian, Ling-ling; Liu, Xiao-yu; Yu, Zhi-ming; Wang, Ru-xing (Frontiers in Physiology, 2020)
Diabetic coronary arterial disease is a leading cause of morbidity and mortality in diabetic patients. Impaired function of large conductance calcium activated potassium channels (BK channels) is involved in diabetic coronary disease. Many studies have indicated that reduced BK channel expression in diabetic coronary artery is attributed to ubiquitin mediated protein degradation by ubiquitin-proteasome system. This review focuses on the influence and mechanisms of BK channel regulation by E3 ubiquitin ligases in diabetic coronary disease. Thus, BK channels regulated by E3 ubiquitin ligase may play a pivotal role in the coronary pathology of diabetic mellitus and, as such, is potentially attractive target for therapeutic intervention.